Electrochemical cycloaddition of hydrazones with cyanamide for the synthesis of substituted 5-amine-1, 2, 4-triazoles. Issue 16 (6th February 2023) - Yang, Minghua; Jiang, Rui; Mu, Yangxiu; Hong, Yu; Wan, Yaya; Hou, Jing; Tang, Dong
Abstract : An eco-friendly and efficient electrochemical method for the synthesis of 5-amine-1, 2, 4-triazole derivatives has been developed by employing hydrazones or in situ generation of hydrazones with cyanamide using KI as the catalyst and electrolyte. Abstract : An eco-friendly and efficient electrochemical method for the synthesis of 5-amine-1, 2, 4-triazole derivatives has been developed by employing hydrazones or in situ generation of hydrazones with cyanamide using KI as the catalyst and electrolyte. This strategy could be smoothly conducted with simple reaction conditions at room temperature without the addition of a chemical oxidant in an undivided cell, and cyanamide has been proven to be of great value in electrosynthesis.